Implementation of the Cooperative Learning Model of the Course Review Horay Type to Improve Student Learning Outcomes on the Material of Vibrations and Waves - Saputri, Debi Eka; Azizahwati, Azizahwati; Irawan, Dedi (Journal of Educational Sciences, 2025)
The low student learning outcomes are caused by the lack of motivation and participation of students in the learning process. This study aims to describe the cognitive learning outcomes of students and determine the improvement in cognitive learning outcomes of students between classes that apply the cooperative learning model of the course review horay type and classes that apply the conventional learning model. The research method used is a quasi-experiment with a pretest-posttest control group design. The results of the descriptive analysis of the experimental class obtained an average value of cognitive learning outcomes of 74.14 in the good category, while the control class obtained an average value of 63.57 in the fairly good category. The results of the hypothesis test obtained 0.000 smaller than 0.05 which means there is a significant difference in cognitive learning outcomes of students between classes that apply the cooperative learning model of the course review horay type and classes that apply the conventional learning model on the material of vibrations and waves in class VIII SMPN 20 Pekanbaru. Thus, it is concluded that the cooperative learning model of the course review horay type is able to improve students cognitive learning outcomes.